Climate change reduces the distribution area of the shea tree (Vitellaria paradoxa C.F. Gaertn.) in Burkina Faso. (October 2020) - Dimobe, Kangbéni; Ouédraogo, Amadé; Ouédraogo, Korotimi; Goetze, Dethardt; Stein, Katharina; Schmidt, Marco; Ivette Nacoulma, Blandine Marie; Gnoumou, Assan; Traoré, Lassina; Porembski, Stefan; Thiombiano, Adjima
Abstract: Vitellaria paradoxa, the shea tree, an economically important fruit-tree species native to savanna regions is threatened in Burkina Faso due to overexploitation and changing land-use. Furthermore, it remains unclear how climate change will influence its frequency and distribution. We investigated the impact of climate change on the projected spatial distribution of favorable habitats for V. paradoxa . Species distribution modeling techniques implemented in MaxEnt combined with GIS were used to forecast the current and future distribution of V. paradoxa . We selected two climatic scenarios (RCP4.5 and RCP8.5) and two global climate models (MPI-ESM-MR and HadGEM2-ES) to encompass the full range of variation in the models. Presence records of the species were collected and linked to bioclimatic and edaphic variables. The most characteristic and least correlated variables were selected for modeling after a collinearity test. Under current climatic conditions, 51% of the national area was found to be favorable for cultivation and conservation of the species. Under future climate projections, our models predict that favorable habitats of this species will decline by 12% (RCP4.5) and 13% (RCP8.5) by 2070. The predictive modeling approach presented here may be applied to other economically important tree species. Highlights: Vitellaria paradoxa is a multipurpose, and agroforestry tree species in West Africa. Species occurrence records were combined with climatic and soil data in MaxEnt. We used the IPCC's RCP4.5 & RCP8.5 emission scenario for 2050 & 2070 for our modeling. Suitable habitats for Vitellaria paradoxa likely to decrease by up to 13.25%. Results could be used as basis in formulating appropriate adaptation policies.